Dynamic response of pipelines under impact and harmonic loading. Issue 1 (15th May 2019) - Pavlou, Dimitrios G.; Correia, José António
Abstract : This study deals with the dynamic response of pipelines under flexural loads. The flexural loads can be harmonic (transmitted by pumps, compressors, etc.) or transient (seismic loads, foundation movement and impact for pipeline inspection). Existing works provide solutions in the frequency domain or in the time domain. However, the methods in the frequency domain cannot simulate the pipeline response under transient loading and the methods in the time domain are mostly based on approximate techniques. An exact solution for pipeline response under transient and harmonic loads is proposed. The modelling of fluid−pipe interaction under transient loading conditions yields coupled equilibrium and motion partial differential equations. Decoupling of the above equations is possible; however, it increases the order of the differential equations from 1 to 4. A system of eight first-order coupled partial differential equations is decoupled, yielding eight fourth-order ones. Integral transforms are used to achieve an analytical solution. The methodology is based on double integral transforms. The implementation of a finite sine Fourier transform for the spatial variable and the analytic inversion of the Laplace transform in the time domain are new. Results are provided for pipelines subjected to impact and harmonic loads.